The Buddhist Doctrine of Anatta in the Filipino Concept of Sarili or Loob: A Cultural Verification - Mijares, Bernabe M. (The PASCHR journal, 2021)
This study entitled "The Buddhist Doctrine of Anatta in the Filipino Concept of Sarili or Loob: A Cultural Verification" used textual analysis of primary, secondary, and tertiary sources. The study concluded that the Buddhist doctrine of anatta could not be verified in the Filipino concept of sarili or loob through the latter’s cultural experiences and practices. However, "a" self of the Buddhists as a "becoming" could be verified in the "becoming or the constitution" of the Filipino self. While the Buddhists favor the flow of causation, the Filipinos anticipate the dialogic encounter to bring about the becoming of the self.